Leprosy in French Polynesia. (May 2019) - Musso, D.; Rovery, C.; Loukil, A.; Vialette, V.; Nguyen, N.L.
Abstract: Leprosy is a neglected endemic infectious disease in the Pacific region. In French Polynesia (FP), leprosy is no longer a public health problem at the national level, defined by the World Health Organization as a prevalence rate below 1 case per 10, 000 population. However, even if its incidence has dramatically declined in FP in the last decades, leprosy is still endemic at a low level. Here we present a case of leprosy in a 34-year-old man from FP diagnosed in 2018. Clinical and microbiologic examinations, including fluorescence in-situ hybridization, led to the diagnosis of a multibacillary leprosy, and multidrug therapy was initiated. There is a need to maintain leprosy surveillance and trained medical staff for the detection and treatment of new cases.